CRITERIA FOR DECIDING ON THE EXERCISE OF PARENTAL RIGHTS AFTER DIVORCE IN THEORY AND PRACTICE - Kovaček Stanić, Gordana; Samardžić, Sandra O. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The article is based on research of case law conducted three times - 30 years ago, 10 years ago and recently in 2016, on the main criteria for awarding a child to one parent for sole custody. The researches were conducted in the courts in Novi Sad and Subotica. In addition, the paper examines the relevant legislation, starting with the laws that were in force before the Second World War to date. By comparing the results of previous research with the newer ones, the main conclusions are that the children are more often entrusted to mothers for sole custody and that the erstwhile criteria for such decisions are similar with nowadays. The most common criterion is the agreement of parents, which the court generally accepts without reservation, without determining whether the agreement is in the best interests of the child. However, the change in referring to the principle of the best interest of the child is noticed since the adoption of the Family Аct in 2005, while this Аct for the first time explicitly regulates the child's best interest as a legal standard. The results of the conducted research show evolution of court practice concerning the child's wish as a criterion, while the wishes of the children are increasingly being respected. When it comes to criteria for awarding a child to a father, it has been noticed that there is a difference in research conducted earlier and now. Namely, the court previously attached great importance to the help that the father had from his mother, while today this fact has lost significance. A more frequent determination and appreciation of the child's opinion on the one hand and the courts’ perception of mother and father as equal parents on the other, we consider a positive shift in terms of the criteria for awarding a child to one parent on sole custody and we hope that such trends in judicial practice will develop even more in the future.